Negligence of Critical Thinking as a Basic Strategy of Management Instruction in the Country - Sayed Aligholi Rowshan (پژوهش‌های مدیریت عمومی, 2016)
This article on the basis of a conceptual research by bringing up a basic problem of management instruction in our universities and using a phenomenological analysis and the purpose of recognition the most appropriate and effective instructional strategy for management studies with a practical solution investigates the genesis and complex nature of the management studies. Through the categorization of knowledge by contemporary German philosopher; Habermas, it is concluded that critical thinking could be a well-known as a basic and the most effective strategy of management instruction by the acquisition of meta-cognition skill. And also, case study is the best method to find the solutions for our practical managerial problems that both of them have been neglected in our traditional instruction. Management studies won’t be attractive for the most students, so long as this belief would be accepted that we need a shift in order to compile the curriculum and texts on the basis of critical thinkingand case studies.